Fenomenologija zavesti (Husserl, Merleau-Ponty in sodobne nevroznanosti) - Somer, Rika Adela (Analiza (Ljubljana), 2025)
Consciousness is one of the most mysterious yet fundamental topics in the philosophy of mind. Although contemporary neuroscience offers increasingly precise descriptions of brain processes, the question of how these processes give rise to subjective experience–feelings, colours, pain–remains unresolved. This paper focuses on the phenomenological approach developed by Edmund Husserl and later expanded by Maurice Merleau-Ponty. Phenomenology does not treat consciousness as an enclosed internal process but rather as intentional directedness toward the world, where meaning emerges within experience itself. Special emphasis is placed on Merleau-Ponty’s understanding of the body as a “lived body,” which constitutes the condition of perception and our embeddedness in the world. The paper further examines the problem of qualia–the question of how subjective experiences transcend objective descriptions–and demonstrates that the phenomenological approach opens a space for dialogue with contemporary theories such as embodied cognition, enactivism, and neuroscience. The article shows that phenomenology does not provide a definitive answer to the question of consciousness, but it can be understood as a complement to modern sciences, offering a more comprehensive insight into the nature of consciousness.
Keywords: consciousness; embodiment; Fenomenologija; intencionalnost; neuroscience; nevroznanost; pornographyintentionality; telesnost; zavest